Konflik China Dan Taiwan Dalam Tinjauan Hukum Internasional - Nunumete, Verly; Wattimena, Josina Augustina Yvonne; Tahamata, Lucia Charlota Octovina (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: It is necessary to know that international law is basically a collection of applicable legal provisions defended by the international community. The current understanding of international law is law that refers to the relationship between one country and another, between a country and international organizations, which give rise to the rights and obligations of each country and international institutions. The Taiwan Air Force reported that at least 19 Chinese fighter jets, including nuclear bombers, entered their Air Defense Identification Zone (ADIZ) air defense zone on Sunday, May 9, 2021. Purposes of the Research: This study aims to study and understand the relationship between China and Taiwan in terms of international law and to examine and understand the penetration of Chinese fighter planes into Taiwan violating Taiwan's sovereignty in terms of international law.Methods of the Research: This research is a normative juridical research by means of research conducted by collecting primary, secondary, tertiary data, obtained by using library research. The data that has been collected is analyzed systematically based on legal disciplines to achieve clarity on the issues to be discussed.Results of the Research: The results obtained from this study are that the territorial sovereignty of the State is the most important thing in the case of relations between China and Taiwan according to international law. The territorial sovereignty of the State is a guarantee in upholding the meaning that the state has full power rights to exercise its territorial rights within the boundaries of its territory. This has been expressly regulated and stipulated in the provisions of international law as international law regulates the state to have the authority to be responsible and overcome violations of sovereignty in the territory of the country. As in the case of the conflict, the intrusion of Chinese fighter planes into Taiwan clearly violated the sovereignty of the State's territory, more specifically the territory of Taiwan, as well as impacted relations for the two countries. contrary to the applicable laws and regulation